Dinamika Kebijakan Pendidikan Agama Islam pada Masa Orde Baru - Nurhayati, Ria (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2025)
Some Islamic education policies during the New Order brought changes to the status of Islamic education. These policies indicate that Islamic education during the New Order era had the authority to develop and participate in efforts to realise the goals of the 1945 Constitution. This article will further discuss the policies of Islamic education and the teaching of Islamic Religious Education during the New Order era. The research was conducted through literature study and qualitative analysis by reviewing literature related to the theme. Various policies have been issued in an effort to improve the quality of national education, including Islamic education. Starting with MPRS Decree No. 27 of 1966, which mandated religious education at all levels of education. The Joint Ministerial Decree of 3 Ministers in 1975, which had a very positive impact on the development of madrasahs, and the UUSPN No. 2 of 1989, which integrated religious education into the national education system. The impact of Islamic education policies during the New Order era had a positive effect on the teaching process of Islamic education. In fact, some of those policies are still relevant to the current education system.